PKMS TRAINING FOR TEACHERS IN MODEL APPLICATION PROBLEM SOLVING LEARNING AT SMPTK JIMERO - Zakiyah Anwar; Rusdi Rusdi (Abdimas Siliwangi, 2021)
Teachers are the spearhead in educating the Nation's children, one of them is the Teachers of Jimero Junior High School in Sorong city, West Papua, Teachers must have the competence to teach students and Teachers must have strategies to be able a design and implement learning so that students are motivated to learn in being of the Covid-19 Pandemic. The anxiety of Teachers SMPTK Jimero with the minimum of all limitations in carrying out the teaching and learning process in schools is a problem that must be addressed immediately. The purpose of this PKMS training is to increase the knowledge and skills of Jimero's SMPTK teachers in implementing the Problem Solving Learning model. This training is carried out in 2 (two) stages of implementation, namely: training to strengthen understanding of the Problem Solving Learning Model and training in teaching practice using the Problem Solving Learning Model, from the results of activities from the participant response answering Strongly Agree the Problem-Solving Learning model training improves understanding and skills participant.